Embracing Risk Factors into Product Redesign Model based on DFMA and Concurrent Engineering: A Review for Research Opportunities - Juniani, Anda Iviana; Setiawan, Tri Andi; Sarena, Sryang Tera; Purnomo, Dhika A; Ningrum, Pranidiya O (SITEKIN: Jurnal Sains, Teknologi dan Industri, 2024)
Product redesign strategies can reduce production costs and shorten design lead times in developing new variants. In the manufacturing design model, identifying the function of components based on customer demand and quality standards becomes vital information for enhancing product reliability, even though design reliability analysis needs to be more frequently addressed. The Design for Manufacturing & Assembly (DFMA) model has been implemented to simplify product structure, reduce risk and manufacturing and assembly costs, and analyze and identify improvement targets. DFMA has evolved into a philosophy for optimizing total production costs from the perspective of assembly, part design, and total life cycle costs. In many studies, the design and development of remanufactured products have been conducted with quality and compliant initiatives. The form and behavior of failure and repair activities obtained during the conceptual design phase have yet to be systematically considered as the basis for product design enhancements. Risk considerations and failure analysis have yet to be utilized as an integrated model during the product redesign phase. This study aims to evaluate the existing DFMA model and develop a new product redesign model and repurposed product with the integration of the Concurrent Engineering (CE)-based Redesign for the Manufacturing & Assembly model by considering reliability and risk factors. Incorporating the model concept is anticipated to contribute to a dependable, efficient design and reduce manufacturing expenses